PROSES SEDIMENTASI DASAR LAUT DI TELUK KUMAI, KALIMANTAN TENGAH, DAN HUBUNGANNYA DENGAN CEBAKAN EMAS DAN PERAK - Usman, Ediar; R.Silalahi, Imelda (Jurnal Geologi dan Sumberdaya Mineral, 2009)
Results of analysis of gold and silver contents within the sea floor sediments in the Kumai Bay show that the highest contents are at the location of TPL-43, TPL-44, TPL-54, TPL-74 and TPL-75 locations with ranging from 0,09 to 0,19 ppm for gold and 1,6 to 3,75 ppm for silver. A curve showing the relationship between grain size and percentage of grain cumulative of gold and silver bearing sediments indicates that the deposition process is a combination pattern between saltation and suspension. The saltation pattern happened at the grain size between -1,5 to 2 phi and suspension pattern 2 - 4 phi. Based on relation curve of the grain size and frequency percentage of the grains indicate the present of a certain grain dominated the depositional process. The most influenced grain size on depositional process are between 0,5 - 2,5 phi that are a medium sand to very fine sand of about 10 - 28%. The depositional pattern of the sediment in the survey area is influenced by the regime of bay current as a combination of the sea and river currents to form the coastal sand sediments. Result of the analysis can become a guidence in gold and silver mining activities in the study area in order to obtain optimal results, that is on sediments with size ranging from medium - very fine sand around the coastline area. Keywords: sediment, gold and silver, depositional process, grain size, Kumai Bay